The Role of Economic Education in the Context of Shaping the Stability of the Financial System - Ratowska-Dziobiak, Eleonora (Journal of Finance and Financial Law, 2021)
An efficiently operating financial system is considered as an integral part of a well-functioning economy. It is the mechanism by which services are provided that allow the flow of purchasing power. Thus, this system creates the foundations of activity for entities using money, enabling the conclusion of economic transactions in which money performs various functions. The result of the existence of this system is the possibility of co-creation of money by non-financial economic entities (enterprises and households) and the flow of cash between them. In the light of many transformations taking place in the financial system, it is extremely important to ensure its stability. A properly functioning financial system significantly supports the achievement of the main goals of the central bank – maintaining a stable level of prices, and thus creating the basis for achieving long-term economic growth. Educational activities are of great importance in ensuring the stability of the financial system. The aim of the article is to present the role of economic education among young people, thanks to which they can better understand the complexities of the functioning of the financial system, the importance of its stability and prepare to make more conscious decisions as fully-fledged participants of the financial market. Understanding the specificity of the available financial instruments enables the minimalization of the risk associated with their selection / purchase. The accuracy of decisions made in adulthood depends on the knowledge of basic economic issues and the awareness of potential threats.